The image of historical tourism in the area of the Ayutthaya Historical Park affecting the decision to visit of Thai tourists in Phra Nakhon Si Ayutthaya - et. al., Dr.Pakamas Chairatana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research study aims to 1) study the personal factors influencing the decision to visit among Thai tourists visiting the Ayutthaya Historical Park area 2) study the image and decision making in the historical tourism in the Ayutthaya Historical Park of Thai tourists. The study was a quantitative research. The sample was 400 Thai tourists traveling to Ayutthaya Province. The research tool was a questionnaire. The data were analyzed by using statistics including frequency, percentage, mean, standard deviation and multiple regression analysis. The results of the research found that the level of opinion on the historical tourism image in the Ayutthaya Historical Park area in terms of the image towards the overall place was at a high level ("x ̅" = 4.17). When considered individually, it was found that the item with the highest average was Ayutthaya Historical Park as a valuable tourist attraction for society and the nation ("x ̅" = 4.34), followed by the Ayutthaya Historical Park, which is a historic tourist attraction ("x ̅" = 4.25), Ayutthaya Historical Park was a valuable tourist attraction in the field of art ("x ̅" = 4.20), Ayutthaya Historical Park was a world famous tourist attraction ("x ̅" = 4.09) and the Ayutthaya Historical Park was a tourist attraction with a revered temple ("x ̅" = 3.99), respectively.